Interactions between African and Global International Societies: the African Peer Review Mechanism (APRM). Issue 3 (3rd July 2015) - Tan,
Abstract : Through an analysis of the African Peer Review Mechanism (APRM), one of the most visible and ambitious governance exercises undertaken by African states, this paper considers the ways in which an African international society and global international society have interacted. The presence of regional international societies implies the presence of difference in global international society, and therefore the possibility of a breakdown in global consensus and the fragmentation of global international society, a perennial concern of the English School. However, while divergences between African and global international societies on democracy and political governance result in tensions, the APRM can be seen as a way to negotiate between these divergent positions. The APRM is an uneasy and unstable compromise, indicating a highly ambivalent relationship between African and global international societies. This relationship has to be understood in the context of an unequal global international society, dominated by a number of core states with an increasingly solidarist governance agenda, as well as the attempts of a largely pluralist African international society to manage its demands.